Test In Silico Compounds Of Lime Leaves (Citrus Amblycarpa (Hassk.) Ochse) As Inhibitors Of Angiotensin Converting Enzyme (ACE) Causes Hypertension - Fitrohrezky Akbar Maulana; Tiara Ajeng Listyani; Anna Fitriawati (International Journal of Health Engineering and Technology, 2026)
Hypertension is a global health problem with high prevalence and is a major risk factor for cardiovascular disease. One of the main mechanisms of hypertension is increased Angiotensin Converting Enzyme (ACE) activity. The use of synthetic ACE inhibitors often causes side effects, such as nausea, hyperkalaemia, headaches, swelling of the lower skin, coughing, taste disturbances, and angioneurotic edema. Therefore, natural-based alternatives are needed. Lime leaves (Citrus amblycarpa) are known to contain various bioactive compounds that have the potential to act as ACE inhibitors. This study aims to analyze the interaction of active compounds in lime leaves with ACE through molecular docking, as well as to predict their ADME profile and toxicity. The study was conducted in silico using PyRx–AutoDock Vina for molecular docking, PyMOL and BIOVIA Discovery Studio for interaction visualization, SwissADME for ADME prediction, and ToxTree for toxicity analysis. Method validation was performed based on an RMSD value < 2Å. The results of the study indicate that 1,3-benzenedicarboxamide is the best compound with an RMSD value of 1.998 Å and a bond free energy (ΔG) of −6.4 kcal/mol, forming specific amino acid residue bonds similar to the native captopril ligand. ADME predictions meet Lipinski's Rule of Five criteria and fall into the low toxicity category (Class I) based on Cramer's rules. The compound 1,3-benzenedicarboxamide has the potential to be developed as a candidate ACE inhibitor for hypertension therapy.